Information search, integration and personalization : International Workshop, ISIP 2012, Sapporo, Japan, October 11-13, 2012. Revised Selected Papers - Spyratos, Nicolas; Yoshida, Tetsuya; Meghini, Carlo; Tanaka, Yuzuru (Communications in Computer and Information Science, 2013)
This book constitutes the refereed post-proceedings of the 7th International Workshop on Information Search, Integration and Personalization, ISIP 2012, held in Sapporo, Japan, in October 2012. The 14 revised full papers presented were carefully reviewed and selected from 29 presentations. The papers are organized in topical sections on knowledge federation and integration; social system support and visualization; social information search and discovery.